A flexible template for informal practical music lessons: A Welsh perspective. Issue 1 (1st April 2021) - Cleaton, Anne
There is a lack of scholarship on informal private popular music lessons compared with school and conservatoire teaching, and informal private music lessons have been viewed as lacking structure. Instrumental teachers often develop strategies from their own experiences, and there is a paucity of recognition of the processes that underpin teachers' knowledge. This article brings into focus indicative examples of my own teaching experiences with my current student cohort, focusing on how specific approaches are informed by a general structure, where teaching approaches are tried, tested and developed. The article contributes to literature on informal popular music teaching developed by the likes of Schulman (1987) and Lucy Green (2001). Key benefits identified in adopting a flexible template for guitar lessons include a growth in student confidence positively affecting their progress and engagement with music.